Knowledge and attitudes about rare genetic diseases among practitioners of oral medicine/pathology in Brazil: a cross-sectional study - Trezena, Samuel; Martelli, Daniella Reis Barbosa; Bonan, Paulo Rogério Ferreti; Graner, Edgard; Sobrinho, Lívia Maria Ferreira; Alawi, Faizan; Coletta, Ricardo D.; Martelli-Júnior, Hercílio (Frontiers in Oral Health, 2025)
IntroductionThis study aimed to analyze the knowledge and attitudes of Brazilian Oral Medicine and Pathology (OM/OP) specialists about genetic diseases.MethodsA cross-sectional and descriptive study was conducted with Brazilian OM/OP specialists, using a pre-structured online formulary. Statistical analyses were performed using Statistical Package for the Social Sciences (SPSS®). The questionnaire was sent to 273 specialists, members of the Brazilian Society of Stomatology and Oral Pathology (SOBEP).ResultsA total of 58 (21.2%) OM/OP specialists responded to the questionnaire. Most of the participants (67.2%) have declared attending theoretical courses on diagnosing and genetic testing for genetic diseases. Furthermore, 79.3% of participants reported that there are barriers to integration between the fields of Medical Genetics and OM/OP. Longer time working as a PhD was associated with knowledge of lesions predictive of genetic diseases (P < 0.05). Dental abnormalities and the presence of tumors, along with Gorlin-Goltz (nevoid basal cell carcinoma syndrome) and Gardner syndromes and neurofibromatosis, were the most frequently reported conditions and recalled by the responders of the survey.ConclusionsThere is limited integration between Medical Genetics and OM/OP. However, there is considerable knowledge about oral manifestations as indicators of genetic diseases among OM/OP experts.